Comparison of Chronic Postsurgical Pain Between Single-Port and Multi-Port Video-Assisted Thoracoscopic Pulmonary Resection: A Prospective Study - Jin, Juying; Du, Xunsong; Min, Su; Liu, Ling (The Thoracic and Cardiovascular Surgeon, 2022)
Background Little is known about the prevalence of chronic postsurgical pain (CPSP) among patients receiving single-port video-assisted thoracic surgery (SP-VATS) compared with those undergoing multi-port VATS (MP-VATS). This study aimed to compare the incidence of CPSP between SP-VATS and MP-VATS lung resection and assess how the pain affected the daily living activities of this patient population.Methods We prospectively collected data regarding the demographic features, clinical factors during surgery, the intensity of acute postoperative pain, and complications after surgery among patients receiving elective SP-VATS or MP-VATS lung resection at our institution between June 2015 and August 2018. At 3-, 6-, and 12-months following surgery, the patients were followed up through a telephonic interview. The Brief Pain Inventory-Short Form was adopted to assess the incidence, severity and location of the CPSP, analgesic consumption, as well as the interference of pain with daily activities.Results In total, 476 patients were screened for eligibility, 411 patients were followed up for 12 months and included in final analysis. Among these, 190 patients had undergone an SP-VATS pulmonary resection and 221 had an MP-VATS pulmonary resection. At both 3 and 6 months, the incidence of CPSP in the SP-VATS group was lower than that in the MP-VATS group (25.3 vs. 38.0%, p = 0.006; 11.1 vs. 19.0%, p = 0.026, respectively). At 12 months after surgery, the prevalence of CPSP was comparable between groups (4.7 vs, 9.0%, p = 0.089). In addition, the SP-VATS technique alleviated pain interference with the daily living activities of patients with CPSP in several domains, including sleep, mood, and enjoyment of life compared with the MP-VATS technique. The two predictive factors for CPSP at postoperative 3 months were the MP-VATS technique (odds ratio [OR] = 1.792, p = 0.019) and postoperative chemotherapy (OR = 1.718, p = 0.033).Conclusions This study indicated that the SP-VATS technique reduced the prevalence of CPSP at 3- and 6-months post-pulmonary resection compared with the MP-VATS technique. The SP-VATS technique also significantly alleviated pain interference with the daily living activities of the patients.
Keywords: Chronic postsurgical pain; single-port video-assisted thoracic surgery (SP-VATS); multi-port VATS (MP-VATS); pulmonary resection